2018
DOI: 10.3892/etm.2018.5825
|View full text |Cite
|
Sign up to set email alerts
|

Immunological changes of T helper cells in flow cytometer‑sorted CD4+ T cells from patients with Hashimoto's thyroiditis

Abstract: Abstract. Recent incidence rates for Hashimoto's thyroiditis (HT) and hypothyroidism are higher than those of previous studies. Previous studies indicated that T helper cells may have a major role in the pathogenesis and development of HT, but there is no consensus in the literature. The aim of the present study was to explore the peripheral T helper cell response in the different stages of HT. In this cross-sectional study, we performed flow cytometry analysis to determine the various T cell subsets of 389 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Concordantly, cytokines that counteract 1 responses, produced by 2 cell subsets and T regulatory cells, has been shown to have a protective effect on autoimmunity [38]. Our previous studies have found that an increased immune deviation of 1 lymphocytes and compensatory accelerating activity of Treg cells in HT patients [39].…”
Section: Discussionmentioning
confidence: 89%
“…Concordantly, cytokines that counteract 1 responses, produced by 2 cell subsets and T regulatory cells, has been shown to have a protective effect on autoimmunity [38]. Our previous studies have found that an increased immune deviation of 1 lymphocytes and compensatory accelerating activity of Treg cells in HT patients [39].…”
Section: Discussionmentioning
confidence: 89%
“…Factors that enhance the possibility of occurrence of HT mainly include genetic factors, immune effects, and environmental influences. Immune mechanisms hold the dominant position 1, 6, 7. However, details of the mechanisms remain ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of HT depends on many elements, including genetic predisposition, environmental implication, and immunological factors. Some HT patients suffer from transient hyperthyroidism during the disease process, but the majority ultimately develop hypothyroidism 6, 7. HT is considered a common autoimmune thyroid disease, as well as the cause of the hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that there was no consensus about whether different thyroid functions affect the proportions of circulating Tregs in HTs, we rechecked the potentially eligible articles and found one additional study [28]. The proportion of circulating Tregs tended to be lower in subclinical hypothyroid (p = 0.74) and euthyroid (p = 0.59) HTs than in HCs, but the same trend was not found in hypothyroid HTs (p = 0.93) ( Fig.…”
Section: Additional Meta-analysismentioning
confidence: 99%